Evaluación de la satisfacción de los visitantes del “Bosque Petrificado de Puyango” cantón Puyango, Provincia de Loja. - Encalada Calva, Dilma Anabel (2023)
Quality is one of the fundamental elements considered by service companies and tourist sites and destinations when offering theirservices to the market; for this reason, they must frequently carry out studies on the quality of services, the results of which will serve to determine the level of satisfaction of users and what strategies to implement to improve the quality of their services. For this reason, this research has the following objectives: to analyze the initial conditions of the Petrified Forest of Puyango, to evaluate the satisfaction in the Petrified Forest of Puyango, and to elaborate a strategic plan of improvements for the tourist management of the Petrified Forest of Puyango To reach this purpose the following methodological process is defined; in first instance, the research approach is determined, which is of quantitative and qualitative type, since through the collection of information it was known which is the degree of perception or satisfaction of the users; It was also established that this is a non-experimental - transectional research, since only the observation of the behavior of visitors who come to the tourist attraction during the year 2022 was carried out, and the SERVPERF Model, which is composed of 22 questions, distributed in five dimensions, applied to a sample of 119 people, was used as a collection tool; additionally, an interview with the BPP personnel was used. To assess the reliability of the instrument, Cronbach's alpha was applied, which obtained a result of 1.0, i.e., the instrument's consistency is high. The main result was that 51% of the visitors expressed their agreement with the services offered by the attraction, and it was also found that the dimension with the highest satisfaction (21%) was empathy. Finally, it is concluded that the quality of service isimproved through the implementation ofstrategies focused on the areas of Advertising, Operational Infrastructure, Environment, Human Resources and Clients.